Study of Knowledge, Attitudes and Behavior Dietary Habits of First Trimester Pregnant Women at Tirtomoyo Health Center II - Rahmi Nurrasyidah; Bernaddeta Retno Dwi Susanti; Sugita Sugita (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2023)
Introduction: The diet of pregnant women has an impact on the fetus. The way to fulfill nutritional needs is to consume balanced nutrition. Shortage event chronic energy (KEK) in pregnant women is one of the influencing factors anemia. The nutritional adequacy of pregnant women affects their nutritional status. There are 6.4% of pregnant women with KEK and 9.6% of pregnant women with LILA <23.5 cm and there are 7.2% of pregnant women with anemia in Tirtomoyo Health Center II. Knowledge, attitude and behavior is the main key to supporting healthy behavior change. Objective: This research was conducted to find out knowledge, attitudes and behavior of pregnant women about eating habits in the first trimester at Tirtomoyo Public Health Center II in Wonogiri Regency. Method: This research is descriptive research. The research population for pregnant women in the first trimester of 90 people was taken as a sample by accidental sampling of 30 people. The research instrument uses a KAP questionnaire that has been tested for validity and reliability. Presentation of data with frequency distribution. Result: Our study showed that only 33.3% of pregnant women had good knowledge about balanced nutrition in the first trimester. As many as 80% of respondents had a positive attitude towards balanced nutrition in the first trimester and 86.7% of pregnant women had a positive attitude towards fulfilling nutrition in the first trimester. Conclusion: Even though the mother's knowledge was limited regarding balanced nutrition, the mother had good attitudes and behavior regarding the diet of pregnant women in the first trimester. Health workers at the Tirtomoyo II health center need to conduct health education about nutrition in pregnant women.